2002
DOI: 10.1097/00003727-200207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Behaviors among Adolescents Attending Rural, Suburban, and Urban Schools

Abstract: This study describes differences in health risk behaviors among 2,017 adolescents attending rural, suburban, and urban school districts in upstate New York. Differences in risk behaviors regarding use of tobacco, alcohol, and illegal substances; sexual activity; and carrying weapons were analyzed. A consistent pattern emerged from the analysis of the data, with rural students at most risk. The findings reinforce the need to focus on the relationship between residence and health risk behaviors, so that interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
2
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 15 publications
4
98
2
7
Order By: Relevance
“…The significant emotional, academic, and physical consequences associated with bullying in general [10], coupled with risk factors unique to rural youth [11], underscore the importance of garnering an increased understanding of bullying in rural populations. Several researchers have applied an ecological framework to study the multiple contexts of bullying and victimization (e.g., [12][13][14]).…”
Section: Introductionmentioning
confidence: 99%
“…The significant emotional, academic, and physical consequences associated with bullying in general [10], coupled with risk factors unique to rural youth [11], underscore the importance of garnering an increased understanding of bullying in rural populations. Several researchers have applied an ecological framework to study the multiple contexts of bullying and victimization (e.g., [12][13][14]).…”
Section: Introductionmentioning
confidence: 99%
“…Nüfus yo¤unlu¤unun az ve geleneksel yap›n›n daha egemen oldu¤unu öngörebilece¤imiz k›rsal bölgelerimizde, fliddet davran›fllar›n›n daha nadir görü-lece¤i düflünülebilirdi. Sonuçlar›m›za benzer olarak, k›rsal alanda yaflayan ergenler aras›nda fliddet davran›fllar›n›n daha yayg›n oldu¤unu gösteren araflt›rmalar yan›nda, fliddet davran›fllar›n›n kentlerde yaflayan ergenler aras›nda daha yayg›n oldu¤unu gösteren araflt›rmalar da vard›r (16,60,61). Bulgular›m›z öncelikle k›rsal alanda olmak üzere okullarda fliddeti önleme programlar›n›n gelifltirilmesi ve yayg›nlaflt›r›l-mas› gerekti¤ini düflündürmektedir.…”
Section: Tart›flmaunclassified
“…A growing body of literature has been devoted to comparing urban and suburban school districts. Much of this literature has evaluated health risk behaviors of urban and suburban adolescent students with results indicating no differences between urban and suburban school students for risk behaviors such as tobacco, alcohol, and illegal substance, as well as sexual activity (Atar & Spencer, 2002;Greene & Forster, 2004;Levine & Coupey, 2003). Green and Forster (2004) found that in some cases, suburban adolescents had greater occurrence of risk behaviors than urban adolescents.…”
Section: School Setting and The Male Voice Changementioning
confidence: 99%